Thomas B. Stevenson correspondence - Stevenson, Thomas B., active 1848.
Letter (Cincinnati) written by Stevenson to Henry T. Duncan relating to Whig party politics and the presidential campaign of 1848. Persons mentioned include Henry Clay, Winfield Scott, and Zachary Taylor.
Positive photocopy produced from original with permission of Alice M. Gibson.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clay, Henry, -- 1777-1852; Duncan, Henry T. -- Correspondence; Scott, Winfield, -- 1786-1866.; Taylor, Zachary, -- 1784-1850.; Whig Party (U.S.); Presidents -- United States -- Election -- 1848.; United States -- Politics and government -- 1945-1953.